2,6-Dimethyl-4-m-tolylcyclohex-3-enecarboxylic acid - Xie, Songwen (International Union of Crystallography, 2008)
The title compound, C(16)H(20)O(2), was synthesized to study the hydrogen-bonding interaction of the two enantiomers in the solid state. The racemate is made up of carboxylic acid RS dimers. Intermolecular O—H⋯O hydrogen bonds produce centrosymmetric R (2) (2)(8) rings which dimerize the two chiral enantiomers through their carboxyl groups. The chirality of this compound is generated by the presence of the double bond in the cyclohexene ring and a chiral axis due to the meta-methyl substituent on the aromatic ring.